2019
DOI: 10.3127/ajis.v23i0.1835
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conceptual framework for social media adoption by non-urban communities for non-profit activities: Insights from an integration of grand theories of technology acceptance

Abstract: This paper describes perceptions of social media as a communication tool and source of information for non-profit activities in non-urban communities. It proposes a conceptual framework predicated on the unified theory of acceptance and use of technology and the information systems success model as theoretical lenses and suggests that four key factors influence the intentions of non-urban communities to adopt and use social media for communication and information of non-profit activities: performance expectanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
(49 reference statements)
1
12
0
2
Order By: Relevance
“…UTAUT is one of the most extensively used models, proved to excel over other prevalent models. Recent studies by [21] extended an application of the UTAUT model by proposing a conceptual framework for predicting social media adoption as a communication tool and source of information for non-profit activities in nonurban communities. [21] suggested four key factors influencing intentions to adopt and use social media; namely, performance expectancy, effort expectancy, social conditions, and facilitating conditions.…”
Section: Technology Adoption Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…UTAUT is one of the most extensively used models, proved to excel over other prevalent models. Recent studies by [21] extended an application of the UTAUT model by proposing a conceptual framework for predicting social media adoption as a communication tool and source of information for non-profit activities in nonurban communities. [21] suggested four key factors influencing intentions to adopt and use social media; namely, performance expectancy, effort expectancy, social conditions, and facilitating conditions.…”
Section: Technology Adoption Modelsmentioning
confidence: 99%
“…Recent studies by [21] extended an application of the UTAUT model by proposing a conceptual framework for predicting social media adoption as a communication tool and source of information for non-profit activities in nonurban communities. [21] suggested four key factors influencing intentions to adopt and use social media; namely, performance expectancy, effort expectancy, social conditions, and facilitating conditions. Further extension of the capability of technology adoption models like the UTAUT model could be useful to demonstrate the greater utility and practical value of UTAUT as a conceptual lens for behavioral modeling in contemporary technology-mediated environments [22].…”
Section: Technology Adoption Modelsmentioning
confidence: 99%
“…been found that performance expectancy has a strong positive association with behavioural intention (Escobar-Rodríguez & Carvajal-Trujillo, 2014;Smith et al, 2013), mobile-based communication technologies (Marriott & Williams, 2018), social media applications (Huang et al, 2018;Lim et al, 2019) and mobile wallets (Madan & Yadav, 2016;Slade et al, 2014). Thus, it is hypothesized that:…”
Section: Generational Cohortsmentioning
confidence: 99%
“…More important, the sharing economy extends marketing thought in the co-creation and co-innovation branch of the marketing literature (Abdul-Ghani et al, 2019; Crick, 2020; Fernandes and Remelhe, 2016; Mostafa, 2016; Whalen and Akaka, 2016), by helping marketers understand how producers and consumers can collectively innovate, create value, and engage in sustainable marketing exchanges in a profitable but inclusive way. Thus, the sharing economy holds great promise for advancing understanding of co-creation and co-innovation interactions between the marketing organisation and its customers in for-profit and non-profit and developing and developed economy settings (Esmaeili et al, 2019; Lim et al, 2019b; London and Hart, 2004; Prahalad, 2005; Zadeh et al, 2019; Zare et al, 2019).…”
Section: What Are the Implications Of The Sharing Economy For Marketimentioning
confidence: 99%